Appropriation of common access natural resources through exploration: A differential game of a claiming rush - Ernst Mohr (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1985)
This paper provides a model of natural resource exploration, where the sole motivation to explore arises from a strategic incentive to preempt competitors. It is assumed that private ownership rights over a finite unexplored and commonly held resource stock can be established through a costly deterministic exploration process. The open-loop and the feedback Nash equilibrium is analysed. It is shown that in between intervals of soaring exploratory activities there may be an interval where exploration is declining over time.
Keywords: 330